2010
DOI: 10.1590/s0370-44672010000100023
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura e propriedades do aço inoxidável austenítico AISI 316L Grau ASTM F138 nitretado sob plasma à baixa temperatura

Abstract: ResumoOs aços inoxidáveis austeníticos possuem restrições para a nitretação nas temperaturas convencionais, próximas de 550ºC, devido à precipitação intensa de nitretos de cromo na zona de difusão. Essa precipitação eleva a dureza, mas deteriora as propriedades de corrosão. O uso do processo de nitretação sob plasma permite introduzir nitrogênio em temperaturas inferiores a 450ºC, levando à formação de uma fi na camada de austenita expandida pelo nitrogênio ( N ). Essa fase possui uma estrutura cristalina mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(12 reference statements)
1
6
0
7
Order By: Relevance
“…However, the elastic modulus of expanded austenite remained unchanged 21 , which enhanced the material wear resistance. Nie, Leyland and Matthews 22 and Tschiptschin and Pinedo 23 have reported that the stresses in the substrate/ coating interface can be minimised by matching the elastic modulus of the coating to that of the substrate, which enhances the system performance. Thus, the formation of expanded austenite should enhance the tribological properties of steel because expanded austenite has a hardening effect and its elasticity modulus is near that of the substrate 23 .…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the elastic modulus of expanded austenite remained unchanged 21 , which enhanced the material wear resistance. Nie, Leyland and Matthews 22 and Tschiptschin and Pinedo 23 have reported that the stresses in the substrate/ coating interface can be minimised by matching the elastic modulus of the coating to that of the substrate, which enhances the system performance. Thus, the formation of expanded austenite should enhance the tribological properties of steel because expanded austenite has a hardening effect and its elasticity modulus is near that of the substrate 23 .…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Nie, Leyland and Matthews 22 and Tschiptschin and Pinedo 23 have reported that the stresses in the substrate/ coating interface can be minimised by matching the elastic modulus of the coating to that of the substrate, which enhances the system performance. Thus, the formation of expanded austenite should enhance the tribological properties of steel because expanded austenite has a hardening effect and its elasticity modulus is near that of the substrate 23 . Figure 13 shows the open circuit potential curves of F-53 steel at different nitriding temperatures over a 4000-second period before the potentiodynamic polarisation tests were performed.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
“…Tradicionalmente, os processos de nitretação aplicados aos aços inoxidáveis, utilizam-se de temperaturas na faixa dos 500 ºC [19] em banhos de sais ou, mais comumente, sob atmosfera nitretante-redutora obtida a partir da dissociação de gás amônia [18].…”
Section: A Nitretação Por Plasmaunclassified
“…Temperaturas mais altas, no entanto, também favorecem a formação de compostos mais estáveis de nitrogênio, como os nitretos de cromo que precipitam na matriz metálica, reduzindo o teor de cromo na superfície e, consequentemente, prejudicando a resistência à corrosão dos aços inoxidáveis [19].…”
Section: A Nitretação Por Plasmaunclassified
See 1 more Smart Citation